Genome Editing in Engineered T Cells for Cancer Immunotherapy - Bonini, Chiara; Chapuis, Aude G; Hudecek, Michael; Guedan, Sonia; Magnani, Chiara; Qasim, Waseem (Human gene therapy, 2023)
Advanced gene transfer technologies and profound immunological insights have enabled substantial increases in the efficacy of anticancer adoptive cellular therapy (ACT). In recent years, the U.S. Food and Drug Administration and European Medicines Agency have approved six engineered T cell therapeutic products, all chimeric antigen receptor-engineered T cells directed against B cell malignancies. Despite encouraging clinical results, engineered T cell therapy is still constrained by challenges, which could be addressed by genome editing. As RNA-guided Clustered Regularly Interspaced Short Palindromic Repeats technology passes its 10-year anniversary, we review emerging applications of genome editing approaches designed to (1) overcome resistance to therapy, including cancer immune evasion mechanisms; (2) avoid unwanted immune reactions related to allogeneic T cell products; (3) increase fitness, expansion capacity, persistence, and potency of engineered T cells, while preserving their safety profile; and (4) improve the ability of therapeutic cells to resist immunosuppressive signals active in the tumor microenvironment. Overall, these innovative approaches should widen the safe and effective use of ACT to larger number of patients affected by cancer.